Income Stability and Sustainability in the Colombian Coffee Supply Chain from the Farmers’ Perspective - Komár, Daniel; Sejkora, Jiří, 1985-; Bič, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
In this thesis, the author examines how smallholder coffee farmers in Colombia can achieve improved income stability and long-term economic sustainability. Four specific aims guided the analysis: I. Analyze income distribution across the Colombian coffee supply chain; II. Identify conditions that reduce dependency on volatile market-based pricing; III. Assess whether these conditions also enable farmers to reach sustainable income benchmarks; IV. And provide practical recommendations based on the findings. The study combines descriptive statistical analysis with crisp-set Qualitative Comparative Analysis (QCA). The empirical part draws on a dataset of 143 coffee lots from the Huila region provided by the Czech importer Chicas Industry. Additional reference data were obtained from the Colombian National Coffee Federation (FNCC), the international C-market, and benchmark thresholds from the Sustainable Coffee Buyer’s Guide (SCBG). The analysis focuses on identifying combinations of structural and commercial conditions that support higher farm gate prices and help farmers reach income levels defined as sustainable. The first aim was fulfilled through a quarterly-based value distribution analysis, which showed that farmers captured, on average, around 60% of the final price. Importers’ margins, however, were found to be substantial and highly variable, indicating their influence on the final price formation. While both farm gate and FNCC prices generally aligned with global market trends, pricing in relationship-based trade displayed a degree of independence from the C-market, suggesting the potential for reduced dependence on global volatility. To address the second aim, QCA was applied to identify conditions consistently associated with above-median farm gate prices. The results highlighted high coffee quality as the most reliable individual predictor of better price outcomes.
This effect was significantly enhanced when combined with long-term buyer-seller relationships and the absence of large-volume contracts. These findings align with the logic of relationship coffee models, where mutual trust, product differentiation, and sustained collaboration play a central role in achieving income stability. The third aim evaluated whether such conditions also supported farmers in reaching income levels defined as sustainable. The analysis demonstrated that 100% of analyzed lots exceeded the SCBG Legal Price benchmark, 96% met or surpassed the Living Income level, and 71% reached the Prosperous Price threshold. In addition, 94% of lots generated profits above the Ingreso Vital benchmark set by the Colombian government for a four-person household in 2023. These findings suggest that smallholder farmers can move beyond subsistence-level earnings under specific trade conditions. The final aim was to provide practical recommendations based on the data. Farmers are advised to focus on improving quality, building long-term buyer-seller relationships, and maintaining manageable contract volumes. Furthermore, institutional support measures should also include training in quality management and contract negotiation, investments in infrastructure, and broader promotion of benchmarking tools such as the SCBG. These recommendations aim to support more stable and sustainable income levels across the sector. The findings are based on a single sourcing context and thus cannot be generalized to the entire Colombian coffee sector. However, the study provides relevant insights into the mechanisms that support fairer value distribution and greater economic resilience in specialty coffee. Future research could extend these findings by incorporating other sourcing models, certifications, and regional comparisons.
Vedoucí práce: Jiří Sejkora
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses